Multicultural Politics: Racism, Ethnicity, and Muslims in Britain by Tariq Modood (USA: University of Minnesota Press, 2005. 240 pages.) (American Journal of Islam and Society, 2005)
Multicultural Politics: Racism, Ethnicity, and Muslims in Britain is an eloquentanalysis of empirical and theoretical observations of multiculturalismin Britain. Modood is an expert on this topic, in particular as he writes froma Muslim perspective. The book consists of two parts: “Racism, Disadvantage,and Upward Mobility,” which discusses ethnic diversity in employmentand educational performance, and “The Muslim Challenge,” which compriseschapters five to nine. The book’s main purpose is to critique theBritish perception, which the author labels a “black-white dualism” (p. 5),and the resultant ignorance surrounding the voices of Asians and otherminorities. Modood argues that the black-white division is complicated bycultural racism, Islamphobia, and a challenge to secular modernity. In his introduction, the author sets the stage by providing a brief autobiographicalbackground of how he embarked on the topic of multiculturalpolitics from a philosophical background. These background details are not“nostalgic self-indulgence … in fact, some of the book’s themes are rootedin descriptions from childhood” (p. 4).Throughout the book, Modood emphasizes the “otherness” of Asians,particularly South Asians in Britain, as it existed before the tragedy ofSeptember 11 and subsequent terrorist attacks. He argues that in the pluralistnation of Britain, “South Asians were treated as [the] undesirable other”(p. 5). Muslims, not blacks, were increasingly perceived as the most threatening“other” to Western society. He further argues that race and racism areintricately entangled in how British Muslims were perceived, and that theirculture was habitually stereotyped and perceived as obstructive to assimilationand integration into British society. The author’s arguments shed lighton how British Asians are empirically subjected to double racism, as comparedto British blacks. Modood acknowledges that this complex situationhas to be considered along with such other variables as “class, gender, geography,and [the] social arena” (p. 7) ...